A CUSTOMER PERCEIVED RISK ON ONLINE PURCHASING BEHAVIOR: A TREND ANALYSIS - Nur Ayuni Syamimi Binti Mohd Arifin; Nurul Aqilah Allysa Binti Hasmuri; Nur Elya Syahirah Binti Norizan; Nur Najwa Nabilah Binti Kasin; Nurin Hanani Binti Zuhari; Khairunnisa’ Binti Yussof (International Journal of Accounting, Finance and Business, 2022)
In the 21st century, online purchasing has gained very important attention in the digital economic cycle. In such a situation, online purchasing became the easiest, simple, effortless and most suitable mode for their shopping. Either it could be grocery shopping, household shopping or others. The trends in online purchasing have dramatically increased due to the outbreak of Corona Virus and movement control orders since Mac 2020. The transformation of technology in the digital economy provides positive significant to the customer. However, any related to the internet and online basis had their own risks. There are various perceiving risks among the online consumer. Hence, this paper aims at presenting the reviews of the literature on perceived risk and Online Purchasing Behavior. The existing literature on determinant factors on online purchasing behaviour in organisations as well individuals is being reviewed. This review will give a holistic understanding of the determinant factors of online purchasing behaviour concept for future researchers and aid to identify the research gap.